Impact of the Food Additive Titanium Dioxide (E171) on Gut Microbiota-Host Interaction - Pinget, Gabriela; Tan, Jian; Janac, Bartlomiej; Kaakoush, Nadeem O.; Angelatos, Alexandra Sophie; O'Sullivan, John; Koay, Yen Chin; Sierro, Frederic; Davis, Joel; Divakarla, Shiva Kamini; Khanal, Dipesh; Moore, Robert J.; et al. (Frontiers in Nutrition, 2019)
The interaction between gut microbiota and host plays a central role in health. Dysbiosis, detrimental changes in gut microbiota, and inflammation have been reported in non-communicable diseases. While diet has a profound impact on gut microbiota composition and function, the role of food additives such as titanium dioxide (TiO2), prevalent in processed food, is less established. In this project, we investigated the impact of food grade TiO2 on gut microbiota of mice when orally administered via drinking water. While TiO2 had minimal impacts on the composition of the microbiota in the small intestine and colon, we found that TiO2 treatment could alter the release of bacterial metabolites in vivo and affect the spatial distribution of commensal bacteria in vitro by promoting biofilm formation. We also found reduced expression of the colonic mucin 2 gene, a key component of the intestinal mucus layer, and increased expression of the beta defensin gene, indicating that TiO2 significantly impacts gut homeostasis. These changes were associated with colonic inflammation, as shown by decreased crypt length, infiltration of CD8+ T cells, increased macrophages as well as increased expression of inflammatory cytokines. These findings collectively show that TiO2 is not inert, but rather impairs gut homeostasis which may in turn prime the host for disease development.